Investigating grade 10 learners' achievements in photosynthesis using conceptual chance model - Tlala, Benedict Mpapa (University of Limpopo (Turfloop Campus), 2011)
A deep level approach to learning leads to quality learning outcomes. Teachers should use appropriate teaching strategies to encourage learners to use deep level approaches to learning. The Conceptual Change Model (CCM) approach is one such strategy for the teaching of science concepts. Deep level approaches are a necessity when dealing with a difficult science concept like photosynthesis. The purpose of this study was to investigate Grade 10 learners’ achievements in photosynthesis using the CCM approach in order to minimize misconceptions and develop a broader and deeper understanding of the photosynthesis process in the high school context in a semi-rural South African school. The learners’ attitudes towards the CCM approach in the teaching of Life Sciences were explored. This study aimed to answer the following main question: what are the achievements of Grade 10 learners’ in photosynthesis as core knowledge? The CCM approach included worksheets based on all five steps of the CCM process: commit to an outcome, expose beliefs, confront beliefs, accommodate the concept and extend the concept. The sample consisted of 78 Grade 10 learners. The research was carried out with a quasi-experimental/control group design and lasted for six weeks. The achievement test and questionnaires were used as instruments to collect data. The analyses of results show that experimental and control group’s pre-test academic achievement scores were similar and there was no significant difference between them (p < 0.05), but when the academic achievement of the post-test results of the EG and CG were analyzed, it was clear that there is a significant difference. The results from post-tests suggest that learners from the EG, taught using the CCM approach, show significantly greater achievements in photosynthesis than learners from the CG. In addition, learners from EG show a positive attitude towards Life Sciences after CCM teaching approach, but not from the CG taught using traditional approach. These findings have implications for a science teacher and recommendations are made to improve the teaching of photosynthesis as core knowledge.
Thesis (M.ED.) --University of Limpopo, 2011
Keywords: Photosynthesis; Chance model; 372.12850968; Education -- Research; Group work in research; Education -- Study and teaching; Education -- Experimental methods -- South Africa